Analysis of the development status of the service sector in the Kashkadarya region - Achilova Firuza Kurbanovna (THE INNOVATION ECONOMY, 2026)
The article analyzes the development status of the service sector in the Kashkadarya region, existing problems, and future prospects. The service sector in the region is considered an important factor of economic growth, and statistical indicators related to tourism, transport, trade, banking and finance, and household services are examined. The study investigates regional disparities, infrastructure capacity, and the level of demand for services among the population.